Dynamic Projection Mapping with a Single IR Camera. (12th February 2017) - Hashimoto, Naoki; Koizumi, Ryo; Kobayashi, Daisuke
Abstract : We propose a dynamic projection mapping system with effective machine-learning and high-speed edge-based object tracking using a single IR camera. The machine-learning techniques are used for precise 3D initial posture estimation from 2D IR images, as a detection process. After the detection, we apply an edge-based tracking process for real-time image projection. In this paper, we implement our proposal and actually achieve dynamic projection mapping. In addition, we evaluate the performance of our proposal through the comparison with a Kinect-based tracking system.